Violência, velhice e políticas públicas: o caso do município de Feira de Santana Bahia - Rovaris, Sonia Cristina (2014)
Violence against the elderly is not a recent phenomenon, although it only came to the interest of the scientific community in the last decades of the 20th century, following the studies of domestic violence. Taking this into account, the present thesis originated from the concern about the huge number of documented cases regarding this kind of violence that can be found at the local office of the Ministério Público do Estado da Bahia which is located in the city of Feira de Santana, Bahia, Brazil. A substantial number of those are rooted in the fragmented state of the structure of public polices aiming at the prevention of such cases. To understand the context in which they happened, we have analyzed all the existing documented cases in the 16ª Promotoria de Justiça de Feira de Santana, during the period from May to September 2012. The motivations for, and the circumstances (social, cultural, environmental...) of the acts of violence were identified, categorized and mapped in the process of analysis, so as to create a sociodemographic profile of the elderly people that were suspected of having suffered violence of some kind, which, in its turn, can be used to subsidize the implementation of specific public policies. To perform the present research we have used the following approaches: exploratory, descriptive, quantitative, qualitative and documentary. From the 215 processes that were analyzed, we have detected that the types of violation of rights suffered by elderly are interpersonal, institutional, healthcare related and also happen when they demand some kid of public service at some government department. 70.2% of the existing complaints were related to interpersonal violence; 21.9% were healthcare related; 3.7% were of institutional violence; 2.4% were not age related aggressions and 1.8% were related to demanding some kid of service at the Ministério Público do Estado da Bahia's local office. Regarding the aggressor's profile the data points towards the national tendency, that is to say, in its majority, the cases of violence against the elderly happen at home, having as its perpetrators close relatives and the like. These represent 61.4% of the analyzed cases. The data also shows that a great number of cases are not being reported by the professionals acting at the specific and non-specific public polices related to the field of elder abuse prevention; the cases are mostly being reported by the victims themselves or by somebody else. We recognize that the quantitative data does not properly reflect the magnitude of the problem, due to the complexity and multiplicity of cases. These situations involve such things as lack of information from the victims, state of denial and negligence from the professionals acting at the field which are themselves ill trained to properly perform their roles